VARIASI KOMPOSISI PEREKAT UREA FORMALDEHIDA DAN BAHAN PENGISI STYROFOAM TERHADAP KUALITAS PAPAN PARTIKEL DARI LIMBAH BATANG KELAPA SAWIT - Zainal Abidin Syah Polem; Tito Sucipto; Rudi Hartono (Program studi Kehutanan USU, 2015)
The waste of oil palm trunks be redundant is alternative basic commodity manufacture particleboards. The purpose of this research was to evaluate the physical and mechanical properties of particle board made from oil palm trunk with variation of urea formaldehyde adhesives and padding Styrofoam particle board. The variation using for the urea formaldehyde adhesives and padding Styrofoam was 100 : 0 %, 90 :10%, 80 :20%, 70 : 30% and 60 :40 %. The boards were made with size 25 cm x 25 cm x 1 cm with density of 0,70% g/cm3. Particleboards using 10% and press 25 kg/cm2 by the padding Styrofoam. The temperatures was 1300 and the pressing times was 10 minute. Particleboards was tested for physical and mechanical properties.The results showed that although the density values ​​ranged from 0.565 - 0.627 g/cm ³, the water content of 7.45 - 8.23​​ %, DSA ​​81.66 - 111.84%, PT 9.99 to 16.35% MOE 6419.87 - 8660.58 kg/cm2, MOR 53.638 - 81.167 kg/cm2 and IB 0.85 - 6.11 kg/cm2. Entire physical properties have fulfilled to SNI 03-2105-2006 standards. All the mechanical properties have not fulfilled to the standards except internal bond with SNI 03-2015-2006 100 treatment: 0 % and 90: 10 %. Keywords: oil palm trunks, urea formaldehyde, styrofoam, particle board, physical and mechanical